2020
DOI: 10.1186/s12887-020-02244-0
|View full text |Cite
|
Sign up to set email alerts
|

Encephalitis due to herpes zoster without rash in an immunocompetent 12-year-old girl: case report and review of the literature

Abstract: Background: Neurological complications due to reactivation of varicella-zoster virus (VZV) are very uncommon in immunocompetent patients. Generally a vesicular rash is present on one or more dermatomes, preceding or following the main manifestation. Few cases are reported in the international literature, but they concern mainly adult or elderly patients. Case presentation: A 12-year-old girl was referred to our hospital for persisting headache, cough and rhinitis for six days. After first examination, diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
2
8
0
1
Order By: Relevance
“…Given the poor bioavailability of oral acyclovir, intravenous (IV) acyclovir is the preferred route [3,11]. IV acyclovir ofers rapid clinical improvement in addition to reduction in long-term complications [12]. Gnoni et al reported a 29year-old immunocompetent patient with VZV meningitis that was successfully treated with IV acyclovir for 2 days followed by oral valacyclovir [13].…”
Section: Discussionmentioning
confidence: 99%
“…Given the poor bioavailability of oral acyclovir, intravenous (IV) acyclovir is the preferred route [3,11]. IV acyclovir ofers rapid clinical improvement in addition to reduction in long-term complications [12]. Gnoni et al reported a 29year-old immunocompetent patient with VZV meningitis that was successfully treated with IV acyclovir for 2 days followed by oral valacyclovir [13].…”
Section: Discussionmentioning
confidence: 99%
“…belongs to the Alphaherpesvirinae group, and causes infection exclusively in humans. 1,2 VZV primary infection (chickenpox) normally occurs in preschool or schoolaged children.1 After the primary infection, the virus remains latent in cranial nerves, dorsal roots, and autonomic ganglia, and it may reactivate years after the primary infection as zoster. 1,3 Both chickenpox and zoster may have neurologic complications, mainly in immunocompromised or older patients.…”
mentioning
confidence: 99%
“…1,2 VZV primary infection (chickenpox) normally occurs in preschool or schoolaged children.1 After the primary infection, the virus remains latent in cranial nerves, dorsal roots, and autonomic ganglia, and it may reactivate years after the primary infection as zoster. 1,3 Both chickenpox and zoster may have neurologic complications, mainly in immunocompromised or older patients. 1,3,4 Reactivation is linked to a decline in cell-mediated immunity, and so, associated with immunocompromised or older individuals, being exceedingly rare in paediatric immunocompetent patients.…”
mentioning
confidence: 99%
See 2 more Smart Citations